1996
DOI: 10.1046/j.1469-0705.1996.08010023.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical vein to artery ratio in fetuses with single umbilical artery

Abstract: In fetuses with single umbilical artery (SUA) the entire blood flow to the placenta is transported through only one umbilical artery, resulting in a compensatory increase of the arterial diameter. In order to establish whether umbilical vessel size could be used as an additional ultrasonographic criterion for prenatal diagnosis of SUA, we measured umbilical vein and umbilical artery diameters in 55 fetuses with SUA and in 55 with a normal three-vessel cord matched for gestational age. In all but one fetus with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 0 publications
3
31
0
5
Order By: Relevance
“…This was initially performed with gray scale 22 and later, with improved accuracy, with the addition of color Doppler 23,24 . Transverse or longitudinal views of the cord may demonstrate the SUA, but it was the identification of the course of the umbilical arteries around the bladder that confirmed the diagnosis 3,6,25,26 . This later technique with color Doppler was utilized in all of our cases.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This was initially performed with gray scale 22 and later, with improved accuracy, with the addition of color Doppler 23,24 . Transverse or longitudinal views of the cord may demonstrate the SUA, but it was the identification of the course of the umbilical arteries around the bladder that confirmed the diagnosis 3,6,25,26 . This later technique with color Doppler was utilized in all of our cases.…”
Section: Discussionmentioning
confidence: 97%
“…The technique to measure the umbilical artery diameter has been described 25,27,28 as the inner diameter on enlarged views of the cord, either in transverse or longitudinal plane. We took care to avoid fetal breathing, which may alter the flow through the vessel, as well as averaging two or three measurements to decrease the risk of error, including pulsatility of the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased diameter of the umbilical artery or similar diameters of the artery and the vein are also sonographic features characteristic of SUA ( Figure 1). It has been suggested that a transverse diameter of the umbilical artery larger than 4 mm or an umbilical vein to artery ratio ≤ 2 is predictive of SUA 16,17 . However, the limitations and pitfalls of such cutoff measurements in the sonographic diagnosis of SUA were recently pointed out 18 .…”
Section: Single Umbilical Arterymentioning
confidence: 99%
“…Compensatory mechanisms allow increase in blood flow through the single artery in order to meet the demands of fetal growth and development throughout pregnancy. 3 Although several studies have reported diminished fetal growth in these pregnancies, [4][5][6][7][8][9][10][11][12] others have not shown differences. [13][14][15] These contradictory findings may be attributed to diverse methodological differences in the published literature.…”
Section: Introductionmentioning
confidence: 99%